Radiations and female fertility - Roberto Marci; Maddalena Mallozzi; Luisa Di Benedetto; Mauro Schimberni; Stefano Mossa; Ilaria Soave; Stefano Palomba; Donatella Caserta (Reproductive Biology and Endocrinology, 2018)
Abstract Hundreds of thousands of young women are diagnosed with cancer each year, and due to recent advances in screening programs, diagnostic methods and treatment options, survival rates have significantly improved. Radiation therapy plays an important role in cancer treatment and in some cases it constitutes the first therapy proposed to the patient. However, ionizing radiations have a gonadotoxic action with long-term effects that include ovarian insufficiency, pubertal arrest and subsequent infertility. Cranial irradiation may lead to disruption of the hypothalamic-pituitary-gonadal axis, with consequent dysregulation of the normal hormonal secretion. The uterus might be damaged by radiotherapy, as well. In fact, exposure to radiation during childhood leads to altered uterine vascularization, decreased uterine volume and elasticity, myometrial fibrosis and necrosis, endometrial atrophy and insufficiency. As radiations have a relevant impact on reproductive potential, fertility preservation procedures should be carried out before and/or during anticancer treatments. Fertility preservation strategies have been employed for some years now and have recently been diversified thanks to advances in reproductive biology. Aim of this paper is to give an overview of the various effects of radiotherapy on female reproductive function and to describe the current fertility preservation options.